Anatomical diversity of the female external genitalia and its association to sexual function. (January 2016) - Krissi, Haim; Ben-Shitrit, Gadi; Aviram, Amir; Weintraub, Adi Yeuda; From, Anat; Wiznitzer, Arnon; Peled, Yoav
Abstract: Objective: To provide data on the anatomical dimensions of adult female genitalia and to investigate the possible association of vulvar morphology and sexual function. Study design: This cross-sectional prospective cohort study, using measurements of the external genitalia was performed in a day-care unit of a tertiary, university-affiliated medical center from 2013 to 2014. Thirty-two premenopausal women aged 20–51 years, undergoing gynecological procedures under general anesthesia (not involving the external genitalia) were asked to respond to both a local general data questionnaire and a validated sexual function questionnaire (PISQ-12). Based on reported orgasmic performance during sexual intercourse, patients were divided into two groups, and the measured genital features were compared. Results: Age, body mass index, parity and sexual activity history were recorded. A wide range of values was noted for each measurement. There was no statistically significant association between external genitalia measurements and age, parity or sexual activity. There was no statistically significant difference in any of the external genitalia measurements between the groups. Conclusion: Wide variability exists in the appearance of female external genitalia. Sexual function does not appear to be associated with genital dimensions. This information is important for both women and surgeons when considering cosmetic vulvar surgery.